Ideal telestroke time targets: Telestroke-based treatment times in the United States stroke belt. (April 2020) - Nalleballe, Krishna; Sharma, Rohan; Brown, Aliza; Joiner, Renee; Kapoor, Nidhi; Morgan, Tiffany; Benton, Tina; Williamson, Conelia; Culp, William; Lowery, Curtis; Onteddu, Sanjeeva
Background: Studying critical time interval requirements can enhance thrombolytic treatment for stroke patients in telestroke networks. We retrospectively examined 12 concurrent months of targeted time interval information in the South Central US telemedicine programme, Arkansas Stroke Assistance through Virtual Emergency Support (AR SAVES). Hypothesi s: We hypothesised that consult data analysis would highlight areas for improvement to shorten overall door to Intra venous (IV) tissue plasminogen activator (tPA) administration time. Methods: We analysed critical time targets for 238 consecutive telestroke neurology consults obtained over 12 months from AR SAVES spoke sites when tPA was administered. The following time intervals were analysed: emergency department (ED) door to Computed Tomography (D-CT); ED door to call centre (D-CC) for initiation of consult; ED door to neurology call (D-NC); neurology call to camera (NC-Cam); tele consult time (Con); ED door to tissue plasminogen activator (tPA)/needle (DTN). Results: The median times of D-CT (13 min, inter quartile range (IQR) 6–22 min), D-CC (34 min, IQR 20–45 min), D-NC (40 min, IQR 21–71 min), NC-Cam (4 min, IQR 2–8 min), and Con (25 min, IQR 17–37 min) all contributed to a DTN median time of 71 min (IQR 50–104 min). A total of 238 patients received tPA with a 29.4% treatment rate and a DTN time of ≤60 min was achieved in 25.2% of patients. Conclusions: Focusing on reducing D-CC and Con times may help to achieve the DTN time of < 60 min for the majority of patients. Having ideal time targets for telestroke patients akin to traditional patients will help identify and improve the overall goal of a DTN time < 60 min.